The Role of Artificial Intelligence Systems in Combating Cybercrime: A Field Study in Jordan - Al-Rawashdeh , Sabah Adel Aref (Jordan Journal of Business Administration, 2025)
This study aimed to identify the role of artificial intelligence in combating electronic crimes in the Jordanian Public Security Directorate/Electronic Crimes Unit. The study population consisted of administration managers and employees of the Cybercrime unit in the Jordanian Public Security Directorate. The interview method and the intentional sample were used for the purposes of representing the study population. The study sample amounted to (132) members. The study relied on the descriptive analytical approach to achieve its objectives, a questionnaire was used to collect data, and the study relied on the statistical program (SPSS) for data analysis. The results of the analysis of the respondents' answers showed that there is a role for artificial intelligence in combating electronic crimes in the Jordanian Public Security Directorate/Electronic Crimes Unit. The study recommended the need to strengthen and benefit from artificial-intelligence systems and programs and employ them in the work of the Electronic Crimes Unit, in addition to working on modernizing and updating them.